Irrigation performance: Mali - Zwart, Sander J.; Kassambara, B.; Schmitter, Petra; Dembélé, Moctar (International Water Management Institute, 2025)
The Irrigation Performance Assessment and Diagnostics Tool (IPADT) provides data-driven insights for infrastructure rehabilitation, integrating high-resolution WaPOR satellite data with field observations to assess irrigation performance.